Use of a Video-Based Case Study to Promote Interprofessional Learning and Collaboration Skills - Robert Wellmon; Linda Knauss; Barbara Gilin; Mary Baumberger-Henry; Normajean Colby; Tracey Rush; Margaret Inman Linn (Association of American Medical Colleges, 2013)
Abstract Introduction Working effectively with other healthcare or human service professionals improves quality of care or service delivery and patient-client outcomes. Interprofessional collaboration occurs in a wide range of practice settings. Academic institutions can play a key role by incorporating learning experiences into professional curricula that prepare students to work effectively on interprofessional teams. However, one of the many challenges faced is finding time in the curriculum to include the necessary learning experiences. To address the challenge and meet the identified need, a 6-hour, case-based, interprofessional learning experience was created. The learning module is incorporated into the professional curriculum for graduate students enrolled in clinical psychology, special education, physical therapy, and social work as well as undergraduate senior nursing students. Methods This learning activity requires a minimum of 6 hours that is distributed across three separate and distinct learning modules. The first two, 1-hour long modules are purposefully discipline-specific and necessary to provide the context and background knowledge for the 4-hour long, capstone interprofessional learning activity, which is a team meeting. The third learning module/team meeting requires collaboration among the students to identify the service needs and plan of care for a student diagnosed with cerebral palsy. The interprofessional team meeting is student led and provides the context for learning from, with, and about the roles that each has as part of the team and the types of clinical decisions that are made by each discipline. Student debriefing and an open discussion conclude the session. Student attitudes toward interprofessional learning and collaboration are assessed prior to and immediately after the learning experience using the Interdisciplinary Education Perception Scale (IEPS), the Readiness for Interprofessional Learning Scale (RIPLS), and the Attitudes Toward Healthcare Teams Scale (ATHTS). Results On the IEPS, significant score improvements were found on the total score, and the examining competency and autonomy, perceptions of actual cooperation, and understanding others' values. On the RIPLS, significant improvements were found on the examining teamwork and collaboration, professional identity, and roles and responsibilities subscales. Regarding the ATHTS, significant improvements were found on the quality of care/team value, cost of team care/team efficiency, and shared leadership subscales. Discussion The educational approach used and related learning activities provided here demonstrate that a relatively short learning experience aimed at changing student attitudes toward interprofessional learning and fostering a level of understanding of the skills required to function effectively on interprofessional teams can be effective. The described educational activities provides a model for creating interprofessional learning experiences that involve other practice settings where collaboration is necessary to provide patient-client services that are not necessarily medically based.